2020
DOI: 10.1186/s12991-020-00265-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for khat use among youth students in Ethiopia: systematic review and meta-analysis, 2018

Abstract: Background: Khat use is a widely spreading public health problem affecting the most economically productive population areas in Ethiopia. Khat use among students has been linked with mental, physical, social, and psychological problems. Reliable prevalence has not been recognized because of varying published rates. The objective of this systematic review and meta-analysis is to synthesize evidence on the prevalence and potential risk factors of khat use in Ethiopia. Methods:We found 284 studies of which 266 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…There has been argument on the similarity ways of consumption between khat and tobacco smoking [ 37 ] (Douglas & Hersi, 2010), and substance intake is frequently observed among men compared to women [ 38 ] (Becker, McClellan & Reed, 2017). Available evidence also showed that the habit of khat chewing reinforces the development of other habits such as cigarette smoking [ 39 ] (Birhane, 2014), as well as the effect of the khat consumption are enhanced mutually with cigarette smoking [ 12 ] (Alemu et al, 2020). The underlying psychobiological mechanisms of this link remain unclear, although it is possible that social cues and pharmacological priming associated with khat use may increase the likelihood and reinforcing effects of smoking [ 35 ] (Nakajima et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been argument on the similarity ways of consumption between khat and tobacco smoking [ 37 ] (Douglas & Hersi, 2010), and substance intake is frequently observed among men compared to women [ 38 ] (Becker, McClellan & Reed, 2017). Available evidence also showed that the habit of khat chewing reinforces the development of other habits such as cigarette smoking [ 39 ] (Birhane, 2014), as well as the effect of the khat consumption are enhanced mutually with cigarette smoking [ 12 ] (Alemu et al, 2020). The underlying psychobiological mechanisms of this link remain unclear, although it is possible that social cues and pharmacological priming associated with khat use may increase the likelihood and reinforcing effects of smoking [ 35 ] (Nakajima et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Many adverse effects have been linked with khat chewing which include impairment of mental [ 37 – 40 ] (Douglas & Hersi, 2010; Becker, McClellan & Reed, 2017; Birhane, 2014; Muluneh, 2018) and physical health such as myocardial infarction [ 10 ] (Al-Motarreb et al, 2002), ischemic heart disease [ 11 ] (Mega & Dabe, 2017), manic-like schizophrenia [ 12 ] (Alemu et al, 2020), erectile dysfunction [ 13 ] (Hassan, Gunaid & Murray Lyon, 2007), psychotic experiences [ 15 ] (Odenwald & Khatkonsum, 2008), oesophageal cancer [ 16 ] (Bozzuto, Ruggieri & Molinari, 2010), stroke, gastritis and hepatitis [ 40 ] (Muluneh, 2018). The urgent need to create better awareness on the potential negative consequences of khat chewing malpractice have been reported in several studies [ 23 , 40 – 43 ] (Alsanosy, Mahfouz & Gaffar, 2013; Muluneh, 2018; Odenwald et al, 2007; Odenwald & Al’ansi, 2017; Wedegaertner et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risky behaviours including alcohol consumption and cigarette smoking are higher among college students than the general population [14][15][16][17][18]. School-based intervention programmes and policy setting on substance use and other risky behaviours are important to reduce the modifiable risk factors of cancer [17]. Therefore, studies at various levels and contexts are important to insight policy makers on the potential area of interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a period of ongoing neurodevelopment that is linked with an increase in risk-taking behaviours, including the onset of substance use. [1][2][3][4][5][6][7][8][9][10][11][12] Substance use causes problems related to increased mortality and morbidity among adolescents and contributes to various forms of mental illness and social complications. [13][14][15][16] Moreover adolescence is a period with significant brain development.…”
Section: Introductionmentioning
confidence: 99%